132k views
4 votes
Solve for x.

-5(x + 1) + 3x - 3= -14
Answer:
Submit Answer
Privacy Policy Terms of Se
Copyright 23201

User SangyK
by
5.2k points

2 Answers

6 votes

Answer:

x = 3

Explanation:

-5(x + 1) + 3x - 3 = -14

Distribute within parenthesis

-5x -5 + 3x - 3 = -14

Combine like terms

-2x - 8 = -14

Add 8 to both sides

-2x = -6

Divide -2 by both sides

x = 3

I hope this helps :)

User Ann Jenny
by
4.9k points
3 votes

Answer:

Let's solve your equation step-by-step.

−5(x+1)+3x−3=−14

Step 1: Simplify both sides of the equation.

−5(x+1)+3x−3=−14

(−5)(x)+(−5)(1)+3x+−3=−14(Distribute)

−5x+−5+3x+−3=−14

(−5x+3x)+(−5+−3)=−14(Combine Like Terms)

−2x+−8=−14

−2x−8=−14

Step 2: Add 8 to both sides.

−2x−8+8=−14+8

−2x=−6

Step 3: Divide both sides by -2.

−2x

−2

=

−6

−2

x=3

Explanation:

User Royg
by
4.0k points